Health and Safety in the Construction Industry in Catanduanes, Philippines - Dexter M. Toyado (International Journal of Engineering and Management Research, 2021)
The Island Province of Catanduanes is gaining grounds in the field of construction. The program of the current administration “Build, Build, Build” have taken the construction industry to full blast. Construction, both private and public are evident on every corners of the island. Occupational Safety and Health in construction is often neglected and disregarded. Construction is the one of the most dangerous sectors in health and safety. The government, thru the Department of Labor and Employment had already address the problem by providing safety and health training to the personnel of the construction firm as well as the industry as a whole. But the effort has been far from satisfactory, as construction accident continue to dominate the entire industry. The study aims to awareness of construction safety in Catanduanes. The study focuses on the awareness of workers in construction industry in Catanduanes on Occupational Safety and Health. From the series of interviews and interaction with the workers on site, and upon evaluation of their responses, the researcher finally come up with the conclusion that, the construction workers are aware of the safety and health in constructions but they do not adhere and follow it. Workers admittedly that the reason they are complaisant about following safety and health practices are discomfort, beliefs, and bad habits. The following recommendation were sought based on the results of the interview; 1. Workers must attend or be trained with safety and health. A training that would enable them to understand the safety and health issues and concerns, 2. Workers must be taught with correct attitude towards safety in workplace, 3. They must taught of right things contrary to their old beliefs, 4. Workers must developed good habit and positive outlook in terms of their safety and well-being.